Menakar Minat Beli Komunitas He Qi Barat dari Ragam Pemantik Merek SayurBox - Halim Agung; Kenny; Rustono Farady Marta (Risenologi, 2021)
Meeting the need for food at this time is changing as technology advances, not to mention the COVID-19 pandemic which requires the need for the use of technology to be urgently needed. The Sayurbox application provides a practical solution to connect buyers and sellers as partners, agents, suppliers, etc. This research was presented with the aim of knowing how much influence electronic word of mouth, brand image, and digital marketing have on the interest in buying products on the Sayubox site in the West He Qi community. Relying on the constructivism paradigm with a quantitative approach, and is explanatory with a simple random sampling technique. The data collection technique was carried out by distributing questionnaires to 93 sample respondents from the West He Qi community with bibliographic sources as secondary data. Hypothesis testing was carried out in this study using a correlation test, coefficient of determination, multiple regression, t test, and F test. The results showed that brand image could not have a significant effect on buying interest, meanwhile electronic word of mouth and digital marketing could have an influence. significant to buying interest.